Morpho- histological study of supraoccipital bone development in domestic rabbit fetuses Oryctolagus cuniculus: Fadhil Sabah Mohammed1and Ahmed Mahdi Saleh2 - Mohammed, Fadhil Sabah (The Iraqi Journal of Veterinary Medicine, 2012)
The developmental study of supraoccipital bone has been done in the rabbit fetuses, which including detection the timing primary appearance and pattern of ossification by using double staining method as well as, histological study which squired for each stages of present study. The double staining technique which are furthering by histological examination for each age, showed the supraoccipital bone was ossify by intramembranous method. The results showed that the primary ossification centers of supraoccipital appeared firstly at(22) day of gestation, and showed direct red staining, at(24) day of gestation, these centers become fused. The supraoccipital bone appear its completely intramembranous ossification at (30) day of gestation and form the roof of foramen magnum.